Effects of fatigue on kinematical parameters during submaximal and maximal 100-m butterfly bouts - de Jesus, K.; de Jesus, Ka.; Figueiredo, P. A.; Goncalves, P.; Vilas-Boas, J. P.; Fernandes, R. J. (Journal of Applied Biomechanics, 2012)
We aimed to analyze the effects of fatigue on kinematical parameters during submaximal and maximal butterfly. Seven female swimmers performed two randomized 100-m butterfly bouts, at submaximal velocity and at maximal velocity in 25-m pool. During the 1st and 4th laps of each 100 m, kinematic data were recorded by two video cameras (above and below water) on the sagittal plane. Velocity, stroke length, stroke frequency, intracyclic horizontal velocity variation, horizontal and vertical displacements of the hand and foot and stroke phases` duration were computed for each stroke cycle. Velocity, stroke length, stroke frequency were lower for 4th than 1st lap, at both intensities. Dropped elbow and foot vertical amplitude of 1st and 2nd downbeats were higher for 4th than 1st lap, at both intensities. At submaximal and maximal intensity, swimmers spent more time during push and recovery phases. At submaximal intensity, swimmers experienced fewer difficulties to cope with fatigue between 1st and 4th lap, which allowed the maintenance of intracyclic velocity variation. However, at maximal intensity, swimmers were probably more fatigued and, as a consequence, less mechanically efficient, showing an increase in intracyclic velocity variation.